Three-dimensional heat transfer analysis of flat-plate oscillating heat pipes. (August 2021) - Odagiri, Kimihide; Wolk, Kieran; Cappucci, Stefano; Morellina, Stefano; Roberts, Scott; Pate, Andre; Furst, Benjamin; Sunada, Eric; Daimaru, Takuro
Highlights: Three-dimensional heat transfer model for flat-plate OHP is proposed. Model includes both thermal hydrodynamic phenomena and thermal diffusion in casing. The model is validated with experimental results of Aluminum flat-plate OHP. Relation of temperature distribution in casing to liquid-vapor behavior is studied. Novel outcome is that moving hot spots on flat-plate OHP surface are evaluated. Abstract: This paper presents a three-dimensional heat transfer analysis of a flat-plate oscillating heat pipe (OHP). To enhance implementation of OHPs in various applications, it is important to understand the comprehensive phenomena that include thermal diffusion in the whole structure and thermal hydraulics in the channel. We developed an OHP model that includes the effect of thermal diffusion and thermo-fluid behavior. The model was validated with experimental results of a flat-plate aluminum OHP which has a size of 200 mm × 90 mm × 3.8 mm, a channel diameter of 1.0 mm, and a turn number of 42. The effect of surface roughness in the channel and liquid film thickness on operating temperature is investigated. The relation between thermo-fluid behavior in the channel and temperature distribution of the OHP is analyzed. For aluminum OHP, the temperature difference across the thickness direction is 0.1 °C which is relatively small, whereas, the moving hot spot: local high-temperature region, is found in the planer surface. The maximum hot spot superheat temperature reached 5.4 °C for 200 W. The novelties of this paper are to develop the three-dimensional comprehensive OHP model and to reveal the combined effect of thermo-hydraulic phenomena and thermal diffusion in OHP structure.